2012
DOI: 10.1007/s10965-011-9777-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced shape memory effect of poly(L-lactide-co-ε-caprolactone) biodegradable copolymer reinforced with functionalized MWCNTs

Abstract: Data from comprehensive thermomechanical tests of poly(L-lactide-co-ε-caprolactone) biodegradable shape memory polymer (SMP) reinforced with pristine and functionalized multiwalled carbon nanotubes (MWCNTs) are reported. The SMP specimens tested up to 500% strain and between 25°C and 70°C temperatures. The incorporation of functionalized MWCNTs leads to the best overall reinforcing effect in tensile modulus, yield stress, tensile strength and elongation at failure. Thermo mechanical experiments resulted that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 43 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…Notably, high shape fixity is crucial for maintaining its temporary shape in the medical devices during applications . Similar findings of low shape fixity of 68–82% were subsequently reported by both Jing et al and Lai et al in their immiscible PLA/TPU blend. , Moreover, the high shape transition temperature ( T trans ) used in this research was also undesirable in biomedical applications. In another approach, the incorporation of compatibilizers such as CNCs, inorganic CNTs, graphene, and others , was employed to improve the miscibility and overall SMP performance. Even so, the resultant SMP often show reduced strain performance and a tedious preparation process.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Notably, high shape fixity is crucial for maintaining its temporary shape in the medical devices during applications . Similar findings of low shape fixity of 68–82% were subsequently reported by both Jing et al and Lai et al in their immiscible PLA/TPU blend. , Moreover, the high shape transition temperature ( T trans ) used in this research was also undesirable in biomedical applications. In another approach, the incorporation of compatibilizers such as CNCs, inorganic CNTs, graphene, and others , was employed to improve the miscibility and overall SMP performance. Even so, the resultant SMP often show reduced strain performance and a tedious preparation process.…”
Section: Introductionsupporting
confidence: 73%
“…24,25 Moreover, the high shape transition temperature (T trans ) used in this research was also undesirable in biomedical applications. 26−29 In another approach, the incorporation of compatibilizers such as CNCs, 30 inorganic CNTs, 31 graphene, 32 and others 33,34 was employed to improve the miscibility and overall SMP performance. Even so, the resultant SMP often show reduced strain performance and a tedious preparation process.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, there are very few reports on shape memory effects of poly(L-lactide) and poly(L-lactideco-ε-caprolactone) copolymers especially on the recovery stress. Cai et al (Lu et al 2008) synthesized poly(L-lactide) and poly(L-lactide-co-ε-caprolactone) and then studied the shape memory effect of the prepared polymers (Lendlein and Kelch 2002;Amirian et al 2012a).…”
Section: Thermosetting Shape Memory Polymersmentioning
confidence: 99%
“…Nabipour Chakoli et al have reported the data from comprehensive thermomechanical and shape memory tests of poly(L-lactide-co-ε-caprolactone) (PLACL), biodegradable SMP that is reinforced with pristine, and functionalized MWCNTs (Amirian et al 2012b), and the main conclusions are as follows:…”
Section: Shape Memory Polymer Nanocompositesmentioning
confidence: 99%
“…However, there still exist some defects such as inconvenience of direct heating, lacking performances and poor mechanical properties. In order to solve these problems and expand the application of SMPs, much attention has been paid to develop novel SMPs triggered by stimuli other than heat recently [6,13,[28][29][30][31][32][33][34]. To this end, metal and carbon-based materials are usually added as the conductive filler preparing electrically actuated SMPs [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%